Oral History Program Interview: Frank Andy Manies - Manies, Frank Andy
Born in Duncan, Stephens County, Oklahoma in 1915, Manies would later join the CCC and use the program to help make his way to Tulare, California around 1934. His interview provides great detail on life in the CCC, discrimination towards "Okies" at work and in town, government and ditch camp life, prejudice against "Okies" and Mexicans, camp stores and "artificial money," perceptions of government aid users, The Grapes of Wrath supporting a negative "Okie" stigma, and organizing and strikes in the fields.